Answer:
Step-by-step explanation:
-6 - (-9)
1) Remove parentheses
-6 + 9
2) Simplify
3
See attachted image for rules of positive and negative integers.
Source: YourDictionary
See the attached picture:
Answer:
Options (1) and (5)
Step-by-step explanation:
Expression that defines the function is,
![f(x)=\frac{1}{2}x+\frac{3}{2}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B3%7D%7B2%7D)
Option 1
![f(-\frac{1}{2})=\frac{1}{2}(-\frac{1}{2})+\frac{3}{2}](https://tex.z-dn.net/?f=f%28-%5Cfrac%7B1%7D%7B2%7D%29%3D%5Cfrac%7B1%7D%7B2%7D%28-%5Cfrac%7B1%7D%7B2%7D%29%2B%5Cfrac%7B3%7D%7B2%7D)
![=-\frac{1}{4}+\frac{3}{2}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B1%7D%7B4%7D%2B%5Cfrac%7B3%7D%7B2%7D)
![=-\frac{1}{4}+1+\frac{1}{2}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B1%7D%7B4%7D%2B1%2B%5Cfrac%7B1%7D%7B2%7D)
![=1+\frac{1}{4}](https://tex.z-dn.net/?f=%3D1%2B%5Cfrac%7B1%7D%7B4%7D)
![=1\frac{1}{4}](https://tex.z-dn.net/?f=%3D1%5Cfrac%7B1%7D%7B4%7D)
So,
is false.
Option 2
f(0) = ![\frac{1}{2}(0)+\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%280%29%2B%5Cfrac%7B3%7D%7B2%7D)
= ![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
True.
Option 3
f(1) = ![\frac{1}{2}(1)+\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%281%29%2B%5Cfrac%7B3%7D%7B2%7D)
= ![\frac{3+1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%2B1%7D%7B2%7D)
= 2
Therefore, f(1) = -1 is false.
Option 4
![f(2)=\frac{1}{2}(2)+\frac{3}{2}](https://tex.z-dn.net/?f=f%282%29%3D%5Cfrac%7B1%7D%7B2%7D%282%29%2B%5Cfrac%7B3%7D%7B2%7D)
![=1+1+\frac{1}{2}](https://tex.z-dn.net/?f=%3D1%2B1%2B%5Cfrac%7B1%7D%7B2%7D)
![=2\frac{1}{2}](https://tex.z-dn.net/?f=%3D2%5Cfrac%7B1%7D%7B2%7D)
Therefore, f(2) = 1 is false.
Option 5
f(4)
![=2+\frac{3}{2}](https://tex.z-dn.net/?f=%3D2%2B%5Cfrac%7B3%7D%7B2%7D)
![=\frac{4+3}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%2B3%7D%7B2%7D)
![=\frac{7}{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7%7D%7B2%7D)
True.
Options (1) and (5) are the correct options.
Answer:
The answer is
![\frac{5}{4} \\](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B4%7D%20%20%5C%5C%20)
Step-by-step explanation:
Area of a rectangle = length × width
Since we are finding the length
<h3>
![length = \frac{area}{width} \\](https://tex.z-dn.net/?f=length%20%3D%20%20%5Cfrac%7Barea%7D%7Bwidth%7D%20%20%5C%5C%20)
</h3>
From the question
area = 5/6 sq. feet
width = 2/3 foot
Substitute the values into the above formula and solve for the length
The length is
![length = \frac{5}{6} \div \frac{2}{3} \\ = \frac{5}{6} \times \frac{3}{2} \\ = \frac{5}{2} \times \frac{1}{2} \\ = \frac{5}{4}](https://tex.z-dn.net/?f=length%20%3D%20%20%5Cfrac%7B5%7D%7B6%7D%20%20%5Cdiv%20%20%5Cfrac%7B2%7D%7B3%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B5%7D%7B6%7D%20%20%5Ctimes%20%20%5Cfrac%7B3%7D%7B2%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B5%7D%7B2%7D%20%20%5Ctimes%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B5%7D%7B4%7D%20)
We have the final answer as
![\frac{5}{4} \\](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B4%7D%20%20%5C%5C%20)
Hope this helps you
To find the surface are youd have to multiply 6 1/2 by 6, because a cube has 6 total sides. so the answer would be 6•6.5 which equals 39